Catholic Universities and Business Schools from Latin American: Commitment Training Leaders with Ethical Attitudes - Rojas Valdez, Kelly (2022)
This article analyzes the contribution of Catholic universities and business schools within the Latin American context, through what they consider relevant to the development of their students' competencies. Through case studies, the visions and missions of these institutions were analyzed and compared in the level of knowledge, skills and attitudes that are most developed by both Catholic and non-Catholic universities and business schools. In the case of non-Catholic institutions, the most relevant competencies are knowledge and skills, while in Catholic institutions knowledge is equally promoted, but more than skills, attitudes are emphasized. In the study carried out, no major differences were found at the level of Latin American countries respect to Peru, in particular, as part of these. The development of attitudes is fundamental to generate a change, which implies a continuous disposition of the person; establishing relationships with others, who do not necessarily think alike. The role of Catholic universities and business schools consist in emphasize those competencies, which will allow the leaders they train to generate those changes that the current and future scenarios require.